Faculty Branding Strategy Bootcamp by Enhancing Social Media Presence in Higher Education - Alhadi, Muhammad Nikmal Anas (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
This research aims to develop and optimize the Faculty's branding strategy in Islamic higher education through social media, focusing on increasing engagement and positive image of the faculty through the bootcamp strategy. This research is driven by the importance of the role of social media in building the image of educational institutions in today's digital era, where effective communication is the key to attracting the attention of a wider audience. The method used in this study is Participatory Action Research (PAR) in the perspective of MacIsaac (1995) which allows direct involvement of the media team and the academic community of the faculty in every stage of strategy development. The findings of the study show that effective strategies to increase engagement include the use of relevant content, the organization of bootcamps for the development of media team competencies, and the involvement of the academic community as faculty brand ambassadors. The findings are expected to provide insight for social media managers, faculties, and other institutional stakeholders in designing better communication strategies and increasing a positive image through the active involvement of all related parties.